Radar perspective on the variability of tropical convection characteristics over the southwestern Amazon and eastern Pacific regions - Paiva Pereira, Luis Gustavo, author; Rutledge, Steven A., author (Colorado State University. Libraries, 2003)
The focus of this study is to evaluate the intra-regional and inter-regional variability of tropical convection characteristics in the southwestern Amazon and eastern Pacific warm-pool regions. Convection is examined using radar data collected during two tropical field experiments: TRMM-LBA (Tropical Rainfall Measuring Mission - Large Scale Biosphere-Atmosphere in Amazonia) and EPIC (Eastern Pacific Investigation of Climate Processes in the Coupled Ocean-Atmosphere System). In each of the two tropical regions studied, two distinct wind regimes have been observed to occur. In the southwest Amazon, one wind regime was called easterly regime and the other westerly regime. These changes in wind regime have been previously shown to be associated with the passage of baroclinic waves in the subtropical parts of Brazil and the formation of a synoptic-scale feature known as the South Atlantic Convergence Zone. In the east Pacific, one wind regime was called the northerly regime and the other southerly regime. The changes in wind regime over the east Pacific have been observed to be associated with the passage of easterly waves. The variability of the convective characteristics is evaluated in each region as a function of time of day and wind circulation. Some of the features used to evaluate the characteristics of convection include convective area, convective fraction, reflectivity profiles, rain rates, warm rain statistics and ice fraction. The results presented in this thesis showed that the easterly and northerly wind regimes more frequently featured characteristics of stronger convection: greater rain rates, greater reflectivities and convective fractions, deeper convective cores and smaller fractions of warm-rain-producing areas. The results also showed that the easterly regime was associated with higher ice fractions. The diurnal cycle results indicated that convection initiates in the morning and peaks in the afternoon over the southwest portion of the Amazon, whereas in the east Pacific the convection initiates after sunset and peaks just before sunrise. Variations associated with wind regime were shown to be more intense in the southwest Amazon. It was also found that the east Pacific region presented larger convective areas and convective fractions than the southwest portion of the Amazon. The eastern Pacific region was also associated with larger fractions of warm rain areas, but overall the fraction of rainfall owed to warm processes was very small and approximately the same in both regions.
Spring 2003.
Keywords: Convection (Meteorology) -- Amazon River Region; Convection (Meteorology) -- Pacific Ocean